Pharmacokinetics and acceptability of once- versus twice-daily lamivudine and abacavir in HIV type-1-infected Ugandan children in the ARROW Trial. - Musiime, V; Kendall, L; Bakeera-Kitaka, S; Snowden, W; Odongo, F; Thomason, M; Musoke, P; Adkison, K; Burger, D; Mugyenyi, P; Kekitiinwa, A; Gibb, D; et al. (2010)
BACKGROUND: No data on once-daily dosing of nucleoside analogues in African children currently exist. We compared the pharmacokinetics (PK) of once- versus twice-daily lamivudine and abacavir treatment using the World Health Organization recommended weight band dosing of scored adult tablets. METHODS: HIV type-1 (HIV-1)-infected Ugandan children aged 3-12 years receiving antiretroviral therapy that included lamivudine and abacavir twice daily (total 150+300 mg, 225+450 mg and 225/300+600 mg daily for 12-<20, 20-<25 and ≥25 kg, respectively) were enrolled in a crossover study. Plasma PK sampling (at 0, 1, 2, 4, 6, 8 and 12 h after observed morning intake) was performed for the twice-daily regimen at steady-state. Children were then switched to once-daily treatment with PK sampling repeated 4 weeks later (with an additional 24 h sample). Acceptability questionnaires were completed at both time points. Daily area under the curve (AUC(0-24)) and maximum concentrations (C(max)) were compared by geometric mean ratios (GMRs). RESULTS: A total of 41 HIV-1-infected children (median age of 7 years) and n=23, n=14 and n=4 in 12-<20, 20-<25 and ≥25 kg weight bands, respectively, were enrolled. Mean AUC(0-24) was 13.0 and 12.0 mg•h/l for once- and twice-daily lamivudine (GMR 1.09, 90% confidence intervals [CI] 0.98-1.20) and 15.3 and 15.6 mg•h/l for once- and twice-daily abacavir (GMR 0.98, 90% CI 0.89-1.08), respectively, with no difference in 3-6 versus 7-12 year olds. C(max) was 76% (lamivudine) and 64% (abacavir) higher on once-daily regimens. For both children and caregivers, once-daily dosing of lamivudine plus abacavir was highly acceptable and strongly preferred over twice-daily. CONCLUSIONS: In children aged 3-12 years, AUC(0-24) of lamivudine and abacavir were bioequivalent on once- and twice-daily regimens. Once-daily dosing of abacavir and lamivudine could provide an alternative dosing strategy for HIV-1-infected children, with high acceptability and strong preference suggesting the potential for improved adherence.